Re-Visualizing History: Towards a New View of the Spanish Invasion of the Andes (1530s) (Quinto Sol, 2026)
In this article, I will discuss how to answer the following questions: How can we visualize patterns embedded in historical texts? How can we map texts and observe narratives? And why do so? To this end, I incorporate digital maps, qualitative visualization, and a careful reading of historical texts. Qualitative, humanistic, and narrative visualizations can complement ethnohistorical efforts to recover knowledge of the Indigenous past during the colonial period. In particular, I will describe the methods I have adapted from various disciplines—including experimental and narrative cartography, literary geography, and data science—to reimagine the Spanish invasion of the Inca Empire (1530s). These procedures allow us to make visible the silences in the texts and reveal what colonial authors concealed. For example, they highlight the importance of Andean allies and diplomacy for the conquest of Peru, as well as how they wrote narratives of domination from centers of colonial power surrounded by a vast Andean territory beyond their control. Likewise, the routes and journeys of armies, embassies, messengers (chaskis), and native spies can be viewed and mapped. Recognizing these activities places Andean peoples at the center of narratives frequently dominated by the Spanish and a few indigenous elites.
Keywords: Colonial History; maps; visualizations; cartography